Study of the effect of different gases parameter in dry etching process on etch rate profile - Zaharah Mohamad
The principal focus of this project is dry etching technique by using the Inductively Couple Plasma -Reactive Ion Etching (ICP-RIE). This final year project is about to understand and control the equipment for dry etches process. The equipment in dry etch process is inductively couple plasma- reactive ion etching (ICP-RIE).